A Multi-site Case Study of Care Coordination Between Primary Care and Specialty Care. Issue 5 (3rd May 2022) - Charns, Martin P.; Benzer, Justin K.; McIntosh, Nathalie M.; Mohr, David C.; Singer, Sara J.; Gurewich, Deborah
Abstract : Background: Care coordination is critical for patients with multiple chronic conditions, but fragmentation of care persists. Providers' perspectives of facilitators and barriers to coordination are needed to improve care. Objectives: We sought to understand providers' perspectives on care coordination for patients having multiple chronic diseases served by multiple providers. Research Design: Based upon our earlier survey of patients with multiple chronic conditions, we selected 8 medical centers having high and low coordination. We interviewed providers to identify facilitators and barriers to coordination and compare them between patient-rated high sites and low sites and between primary care (PC)-mental health (MH) and PC-medical/surgical specialty care. Subjects: Physicians, nurses and other clinicians in PC, cardiology, and MH (N=102) in 8 Veterans Affairs medical centers. Results: We identified warm handoffs, professional relationships, and physical proximity as facilitators, and service agreements, reporting relationships and staffing as barriers. PC-MH coordination was reported as better than PC-medical/surgical specialty coordination. Facilitators were more prevalent and barriers less prevalent in sites rated high by patients than sites rated low, and between PC-MH than between PC-specialty care. Discussion: We noted that professional relationships were highly related to coordination and both affected other facilitators and barriers and were affected by them. We suggested actions to improve relationships directly, and to address other facilitators and barriers that affect relationships and coordination. Among these is the use of the Primary Care Mental Health Integration model.